MORPHO-FUNCTIONAL ORGANIZATION OF THE SPLEEN OF THE LABORATORY ANIMALS - Авілова, О.В.; Приходько, О.O.; О. O Трач,; Ярмоленко, О.С. (World of Medicine and Biology, 2016)
The spleen that is present in all vertebrates and most functional in mammals is a peripheral organ of hematopoiesis and immune protection. Loss of spleen or structural damage leads to the significant disorders of the immune system. Its functions are provided by two main compartments - white pulp and red pulp, which greatly differ in their structure, vascular and cell organization. The article provides data on the morphology of these components and, to a lesser extent, their function.
Keywords: rats; mice; red pulp; spleen; white pulp